Residential property development in Mactan Cebu formulating a development scheme to capture the informal economy - Gonzaga, Gemma Sheila C. (College of Architecture, University of the Philippines Diliman, 2009)
Residential property development in Mactan is analyzed in this study through a careful evaluation of existing property development projects in the area, taking into consideration the public and private institutions housing loan terms and conditions, laws and regulations that affect property development, economic features, geographic and demographic profile of informal economy. The findings revealed some factors that hinder the entry of informal income earners into planned communities. These are obviously a manifestation of the restrictions and documentary requirements needed to obtain a housing loan in private and government financing agencies. The study shows that regardless of economic activities and geographic features, "informal families" can be unanimous in certain aspects in their development of residential dwellings. In this regard, they will adapt beyond economic and geographic limitations and reflect no great variations in their attempt to create income generating activity within the convenience of their home and beyond in their quest for financial returns.